2012
DOI: 10.1002/jat.2792
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle‐induced oxidative stress, genotoxicity and apoptosis in cultured cells and animal tissues

Abstract: Silver nanoparticles (AgNPs) have emerged as an important class of nanomaterials for a wide range of industrial and medical applications. However, the unique properties of AgNPs could potentially lead to unexpected hazards to both human health and the well being of the environment. Possible mechanisms of AgNP-induced toxicity include the stimulation of oxidative stress, genotoxicity and apoptosis. In this study, a number of previous studies are therefore summarized that demonstrate oxidative stress-, genotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
208
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(231 citation statements)
references
References 74 publications
9
208
0
2
Order By: Relevance
“…Generation of reactive oxygen species (ROS) by the Ag NPs has also been considered a primary mode of cytotoxic action of Ag NPs [22,29]. Several studies observed a high level of ROS in cells treated with Ag NPs [30][31][32][33].…”
Section: Role Of Agmentioning
confidence: 99%
“…Generation of reactive oxygen species (ROS) by the Ag NPs has also been considered a primary mode of cytotoxic action of Ag NPs [22,29]. Several studies observed a high level of ROS in cells treated with Ag NPs [30][31][32][33].…”
Section: Role Of Agmentioning
confidence: 99%
“…Oxidative stress in turn plays an important role in many types of cellular injury, which can result in DNA damage and apoptotic cell death. [63][64][65][66][67][68] ROS are chemical species that are produced as by-products of cellular oxygen metabolism, which occurs via mitochondrial respiration in eukaryotic cells. [63][64][65][66][67][68] AgNPs are capable of producing ROS.…”
mentioning
confidence: 99%
“…Abnormal accumulation of ROS is called oxidative stress, and can lead to serious cellular damage. [63][64][65][66][67][68][69][70][71] According to a literature survey, currently there is limited information available about the mechanism of AgNP-induced toxicity. To know the effect of AgNPs on oxidative stress, we measured ROS generation using the H 2 DCF-DA assay.…”
mentioning
confidence: 99%
“…Fact based prime level research propounded that large size AgNps causes chondrosomic respiratory chain autophagy and for that regenerate oxygen sensory genus tension [2][3][4][5][6][7][8][9]. Vertebrate primate affecting bacterial stem cells are evidenced to be disrupted by bigger size AgNps and have the capability to arise demolition of reproductive, digestion activities [10].…”
Section: Journal Of Nutritional Disorders and Therapymentioning
confidence: 99%